2005
DOI: 10.1098/rspb.2005.3331
|View full text |Cite
|
Sign up to set email alerts
|

The dilemma of female mate selection in the brown bear, a species with sexually selected infanticide

Abstract: Because of differential investment in gametes between sexes, females tend to be the more selective sex. Based on this concept, we investigate mate selection in a large carnivore: the brown bear (Ursus arctos). We hypothesize that, in this species with sexually selected infanticide (SSI), females may be faced with a dilemma: either select a high-quality partner based on phenotypic criteria, as suggested by theories of mate choice, or rather mate with future potentially infanticidal males as a counter-strategy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 50 publications
5
91
0
Order By: Relevance
“…When available, the radiocarbon ages of each specimen was converted in number of generations assuming a value of 12.5 years as mean generation time, in agreement with what is reported for current populations (41). Otherwise, the age of a specimen was inferred from the excavation context; when such information was missing, the age was assumed as equal to the average of absolute ages of the specimens belonging to the same time period.…”
Section: Dna Extraction From Modern Brownmentioning
confidence: 99%
“…When available, the radiocarbon ages of each specimen was converted in number of generations assuming a value of 12.5 years as mean generation time, in agreement with what is reported for current populations (41). Otherwise, the age of a specimen was inferred from the excavation context; when such information was missing, the age was assumed as equal to the average of absolute ages of the specimens belonging to the same time period.…”
Section: Dna Extraction From Modern Brownmentioning
confidence: 99%
“…This included hunter-killed males, accidental deaths, damage-control kills, and radio-collared males (arithmetic center of the 95% MCP home range) suspected to have been killed illegally. A 40-km radius was chosen, because 95% of all fathers of cubs in Scandinavia are within this distance from the mothers (Bellemain et al 2006b). A time lag of 1.5 years was chosen, because Swenson et al (1997) have shown that cub loss was highest 1.5 years after an adult male died.…”
Section: Male Turnovermentioning
confidence: 99%
“…A time lag of 1.5 years was chosen, because Swenson et al (1997) have shown that cub loss was highest 1.5 years after an adult male died. We deWned an adult as ¸3 years of age, because the Wrst age of male reproduction is 3 years in both study areas (Bellemain et al 2006b;Zedrosser et al 2007a). The software package Ranges 6 (Anatrack, Wareham, Dorset, UK) was used for calculating home range centers.…”
Section: Male Turnovermentioning
confidence: 99%
See 1 more Smart Citation
“…The male was also the father of the mother of the described cub, and 2 years later, this female successfully raised two cubs fathered by the same male. In brown bears, inbreeding generally is uncommon (Bellemain et al 2006); however, in very small populations, as in Austria, it may occur more often. It remains unknown if inbreeding in brown bears is associated with abnormalities such as the described case.…”
Section: Discussionmentioning
confidence: 99%